2014
DOI: 10.1007/s11244-014-0310-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Coupling of Methane in Small Scale Parallel Reactors

Abstract: In this work the testing of high temperature reactions in small scale parallel reactors is explored using the oxidative coupling of methane as an example. The advantages of small scale reactors for this very exothermic and complex reaction are discussed. The data generated in this study is explored making use of response surface models derived from statistically designed experiments. Methane conversion has been explored over a Mn-promoted Na 2 WO 4 /SiO 2 catalyst over the temperature range 755-875°C, pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Now, the dataset is subdivided to compare the performance of different catalysts. In the previous HTS research, the performance of OCM catalysts was measured at one or a few fixed conditions. , Meanwhile, our dataset provides the performance of 59 catalysts over a sufficiently wide range of reaction conditions. One obvious profit of such a dataset is that the potential of different catalysts is fairly evaluated at respective sweet spots.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, the dataset is subdivided to compare the performance of different catalysts. In the previous HTS research, the performance of OCM catalysts was measured at one or a few fixed conditions. , Meanwhile, our dataset provides the performance of 59 catalysts over a sufficiently wide range of reaction conditions. One obvious profit of such a dataset is that the potential of different catalysts is fairly evaluated at respective sweet spots.…”
Section: Resultsmentioning
confidence: 99%
“…A safety management system also backups the automation. Here, it is worth noting that HTS instruments having more or less similar mechanic design were reported in the literature, but these instruments were mostly used for catalyst screening at one or a few fixed conditions. Our instrument enables the acquisition of a dataset that covers a parametric space for both catalysts and process conditions by means of parallelization and automation, respectively.…”
Section: Experimental and Analytical Detailsmentioning
confidence: 99%
“…Ras and Gomes-Quero [227] developed small-scale packed-bed OCM reactors operating at temperatures between 755 and 875 • C. They showed that the small- Gas-phase species continuity…”
Section: Reactor Technologiesmentioning
confidence: 99%
“…This is not the case here, as the quadruplicate test of diluted extrudates shows a difference no greater than 0.1 °C, which makes the observed difference in activity between diluted and undiluted extrudates statistically significant. This accuracy is due to the small scale of the experiment and well‐defined hydrodynamics – reducing heat effects by optimizing heat transfer and due to the use of parallel reactor technology – reducing typical run‐to‐run variability compared to single reactors.…”
Section: Resultsmentioning
confidence: 99%